von Willebrand disease: practical considerations for the dentist. Literature review. - Navas-Aparicio, María del Carmen (2022)
von Willebrand disease is the most common inherited bleeding disorder, caused by von Willebrand factor deficiency, which causes defective platelet adhesion and aggregation. It is characterized by a prolonged bleeding time and partial thromboplastin time, with low levels of factor VIII, and increased capillary fragility, but with a normal platelet count. Dental treatment in a patient with von Willebrand disease must be individualized according to the severity of the patient’s condition, as well as coordinated with the hematologist, who must determine the type of disease and the need for factor replacement therapy, prior to the patient management. Through this bibliographic review, it wants to reinforce the dentist’s knowledge of this bleeding disorder, since this can prevent or minimize possible bleeding complications during dental treatment.